BLENDED LEARNING DAN FLIPPED CLASSROM, TREND METODE PEMBELAJARAN MASA PANDEMI COVID-19 - Hamdani Hamdani (WIDYABORNEO, 2021)
Blended learning is a learning method that uses slices of online learning systems (online) and face-to-face learning through video conferences. Flipped Classroom is a reverse classroom learning method, in which the teacher presents recorded material in the form of audio, video, presentation slides online on YouTube so that students can access and study before activities in class in the form of question and answer sessions, discussions. exercise, or other learning activities. This study aims to: (1) describe the classification of teachers application of the blended learning method in Islamic Educational Institutions, (2) describe the teacher's implementation/application of the flipped classroom learning method in Islamic Educational Institutions. The method used in this research is descriptive research with a quantitative approach. The object of research is the application of blended learning and flipped classroom in Islamic Education Institutions. The subjects to be studied are teachers at Madrasah Aliyah Negeri 3 Banjarmasin in the application of blended learning and flipped classrooms. Data collection using a questionnaire sheet. Data were analyzed using percentage analysis and classification of the application of blended learning and flipped classroom. The results of the study are (a) the frequency of application of blended learning in the classification: traditional 0 (0%), web facilitated 9 people (32%), blended 9 people (32%), and online classification 10 people (36%); (b) the frequency of application of the flipped classroom is 15 people (57%) and the traditional classroom is 12 people (43%).